Efficacy and safety of fractional CO2 laser and tranexamic acid versus microneedling and tranexamic acid in the treatment of infraorbital hyperpigmentation. (3rd April 2022) - Ghandehari, Reza; Robati, Reza M.; Niknezhad, Nasim; Hajizadeh, Nastaran; Tehranchinia, Zohreh
Abstract: Objective: To compare the efficacy and safety of microneedling and fractional CO2 laser in combination with tranexamic acid (TA) in the treatment of infra-orbital hyperpigmentation. Patients and methods: This split-face clinical trial performed on 30 volunteers. The patients were randomly assigned to treat with fractional CO2 laser and microneedling, both combined with TA topically. Three monthly treatment sessions were performed. Two blinded dermatologists evaluated the response after each treatment session and one and three months after the last session. We also asked patients to evaluate their overall satisfaction at the final follow up. Adverse effects have also been documented. Results: Both methods showed significant improvement in all sessions comparing with the baseline state ( p value <.05). There were no significant differences between two methods on the days 30, 90, and 150. But the laser showed significantly higher improvement on day 60. The patients' satisfaction did not reveal any significant difference between the two sides. Adverse events were temporary with no significant difference between both sides except for erythema that lasts longer with microneedling. Conclusions: Both fractional CO2 laser and microneedling in combination with topical TA seem to be effective modalities in the treatment of infraorbital hyperpigmentation with no significant side effects.